6(6+(-2c))=60

Simple and best practice solution for 6(6+(-2c))=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6+(-2c))=60 equation:


Simplifying
6(6 + (-2c)) = 60
(6 * 6 + (-2c) * 6) = 60
(36 + -12c) = 60

Solving
36 + -12c = 60

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + -12c = 60 + -36

Combine like terms: 36 + -36 = 0
0 + -12c = 60 + -36
-12c = 60 + -36

Combine like terms: 60 + -36 = 24
-12c = 24

Divide each side by '-12'.
c = -2

Simplifying
c = -2

See similar equations:

| 3+5x=50+x | | 2(t-3)-4=t-3(t+1) | | 3.6=1.6w+24 | | -7-m=-8(8-7m) | | 4r+3=7-(-4r) | | -3x+40=1 | | =-25x+9 | | 4n=368 | | 7(x-1)=11.2 | | =5x-3[(11x-5)-(x-2)] | | 3-2(a-1)=4a-13 | | 5.2=2c-9 | | z^2+2iz-3i=0 | | 4(x-2)+12=2(5-2x) | | 20+X=51 | | 6e-8=16 | | -y+7(6+2y)= | | 2x+12=68+6x | | 5x+2y^2=3 | | (h-78)/9(1)+(-13)+50-(78*.25)=-20 | | 4(2x-1)=-28 | | 4(x-8)=0 | | 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) |

Equations solver categories